Investigating The Zoom Application as A Video Conferencing Platform in The Online Learning Process Based on Teacher's Perception - Gede Rasben Dantes; Ira Putri Audina; Ni Putu Era Marsakawati; Ni Komang Arie Suwastini (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2022)
The use of the Zoom platform is one solution in supporting the implementation of online learning, which still has advantages and disadvantages in its application and utilization. This study explores teachers' perceptions about using this platform and its advantages and disadvantages in teaching and learning. This research was qualitative, following the Model of Qualitative Data Analysis by Miles, Huberman, and Saldaña (2014). The data were collected through open-ended questionnaires through Google Form, involving 12 foreign language teachers. The study revealed that teachers found Zoom very useful in teaching and learning, especially during this pandemic period in delivering and explaining learning materials because Zoom provides various helpful features that support foreign language learning. Teachers perceived Zoom as an effective platform to facilitate online learning. However, teachers also admitted several challenges in using Zoom in their foreign language teachings, such as unstable connection, expensive internet credit, and time limitations.